1973
DOI: 10.1159/000127685
|View full text |Cite
|
Sign up to set email alerts
|

Does Hepatic Blood Flow Decrease after Portal-Systemic Shunt?

Abstract: The precise effect of portacaval shunt upon liver blood flow is still under discussion. In the present work, the consequences of portal-systemic shunt on hepatic blood flow were investigated in rats with normal liver. Hepatic blood flow was measured 24 h after a portacaval shunt according to the technique of constant Bromsulphalein infusion. There was no decrease of hepatic blood flow. Thus, at that time in the rat the increase in the hepatic arterial flow was able to totally compensate portal blood diversion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Until recently, quantitative information on hepatic blood flow in the shunted rat was not available. In 1973, Chauvaud et al (2) investigated hepatic blood flow in rats, 24 h after a portacaval shunt. These authors found no significant modification in hepatic extraction efficiency of BSP nor in total hepatic blood flow after end-to-side portacaval shunt in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, quantitative information on hepatic blood flow in the shunted rat was not available. In 1973, Chauvaud et al (2) investigated hepatic blood flow in rats, 24 h after a portacaval shunt. These authors found no significant modification in hepatic extraction efficiency of BSP nor in total hepatic blood flow after end-to-side portacaval shunt in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…These attempts failed to yield long surviving trans plants for the following reasons: The vascular resistance ultimately deter mined by the capillary bed forms a natural threshold for the flow pres sure. Alterations in the normal flow and intrasinusoidal pressure can at least be partially compensated, for instance by changes in the caliber of intrahepatic arteriolar sphincters [5].…”
Section: Discussionmentioning
confidence: 99%